Promotion of Social Values Among Young People as a Pedagogical Ideology (a Case Study of Russia and Kazakhstan) - Syrymbetova, L.S.; Muratova, L.M.; Smolyaninova, O.G.; Zhilbaev, Zh.O.; Kulsharipova, Z.K. (Journal of Siberian Federal University. Humanities & Social Sciences, 2021)
The article deals with the promotion of national values among students in the context of pedagogical ideology. The authors are convinced that the understanding of ideology is not limited to politics and standards of sociality. In their view, ideology is broader than a means of legitimizing power claims or political expansion, it means having a core value. In the pedagogical context, ideology is a set of social and pedagogical values for building the desired society. In this context, the promotion of social values among students is a systematic set of tools for the realization of pedagogical goals and the formation of social ideals. In the era of globalization, social values are undergoing a significant rethinking. In this context, the problem of promoting universal and national values should be solved in their dialectical unity. In this regard, the authors of the given article have conducted a comparative study of the level of involvement in social values among representatives of universities in Russia and Kazakhstan. The authors have a little deeper outlined the features of the formation of social values in Kazakhstan, in which nowadays a system of social values has been set at the national level, which was set out in the program article of the First President of Kazakhstan, Nursultan Nazarbayev, «Looking to the future: modernization of public consciousness». This program, known as the «Rukhani Zhangyru» spiritual revival program, was launched in 2017. But so far, the values of the «Rukhani Zhangyru» program have not been given a pedagogical interpretation that would allow us to present a holistic conceptual picture of their promotion in the university environment. This is evidenced by a number of studies, including the study and analysis of various publications in the media (mass media, central and regional newspapers), a survey among teachers and students of a number of universities in Russia and Kazakhstan. The results of these studies, detailed in this article, allowed the authors to draw conclusions about the feasibility of developing a holistic concept for promoting the values of the «Rukhani Zhangyru» program in the university environment. Meeting the requirements of the pedagogical ideology, the proposed concept can be applied in any university in Russia and Kazakhstan with a certain degree of its adaptation to the specific conditions of each individual university.
Keywords: spiritual revival; student youth; university environment; social and pedagogical values; promotion of values; pedagogical ideology